Analisis Yuridis Perkara Wanprestasi Transaksi Jual Beli Online Pada Putusan Pengadilan Nomor 629/Pdt.G/2020/Pn Jkt.Sel : Upaya Hukum Dan Perlindungan Konsumen - Novita Fitria Azzahra; Farchanza Haykanna Pireno; Fitrya Putry Amanda; Nadifa Keyla Ismail (Lembaga Pengembangan Kinerja Dosen, 2024)
With increasingly sophisticated technological developments, all sales and purchase transactions can be carried out online through various platforms including websites, social media, e-commerce and other platforms. However, online transactions can cause legal problems. One of the legal problems that often involves the sale and purchase agreement between the seller and the buyer is a breach of contract. Court Decision Number 629/Pdt.G/2020/PN Jkt.Sel is one of the cases of online sale and purchase breach involving Celvin as the buyer as the Plaintiff with Satrya as the owner of the brand